IMPLEMENTATION OF ISLAMIC AGROPRENEUR SCHOOL IN DEVELOPING COMPETENCE NATIONALISM INSIGHT - wahidi, Hasbi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2020)
Islamic boarding schools have the potential to improve people's lives. For that pesantren must have education system innovations based on life skills. This is to improve the quality of its graduates, one of which is through the Islamic Agropreneur School. The purpose of this study is to find out the appropriate educational model for pesantren to produce graduates who are able to compete and apply the concept of Islamic Agropreneur School in pesantren. The approach used in this study is a qualitative approach with an inquiry-naturalistic method. The results showed that the education strategy to improve the quality of HR consists of two models, namely the education strategy that is macro and the education strategy that is micro.